Insulin directly regulates the circadian clock in adipose tissue - Tuvia, Neta; Pivovarova-Ramich, Olga; Murahovschi, Veronica; Lück, Sarah; Grudziecki, Astrid; Ost, Anne-Catrin; Kruse, Michael; Nikiforova, Victoria J.; Osterhoff, Martin; Gottmann, Pascal; Gögebakan, Özlem; Sticht, Carsten; et al. (Diabetes, 2021)
Adipose tissue (AT) is a key metabolic organ which functions are rhythmically regulated by an endogenous circadian clock. Feeding is a “zeitgeber” aligning the clock in AT with the external time, but mechanisms of this regulation remain largely unclear. We tested the hypothesis that postprandial changes of the hormone insulin directly entrain circadian clocks in AT and investigated a transcriptional-dependent mechanism of this regulation. We analyzed gene expression in subcutaneous AT (SAT) of obese subjects collected before and after the hyperinsulinemic-euglycemic clamp or control saline infusion (SC). The expressions of core clock genes PER2, PER3, and NR1D1 in SAT were differentially changed upon insulin and saline infusion, suggesting insulin-dependent clock regulation. In human stem cell-derived adipocytes, mouse 3T3-L1 cells, and AT explants from mPer2Luc knockin mice, insulin induced a transient increase of the Per2 mRNA and protein expression, leading to the phase shift of circadian oscillations, with similar effects for Per1. Insulin effects were dependent on the region between −64 and −43 in the Per2 promoter but not on CRE and E-box elements. Our results demonstrate that insulin directly regulates circadian clocks in AT and isolated adipocytes, thus representing a primary mechanism of feeding-induced AT clock entrainment.
Gesehen am 27.01.2023